A bibliometric analysis of macrophage-associated immune regulation in atherosclerosis: advances in the mechanisms of pathogenesis - Jiang, Meiling; Han, Tianci; Li, Xianhui; Zhu, Guofu (Frontiers in Immunology, 2025)
BackgroundThe occurrence and development of atherosclerosis (AS) is closely related to immune regulation. Macrophages serve as the primary immune cells involved in AS. However, the mechanisms underlying macrophage-mediated immune regulation in AS remain inadequately understood, necessitating the development of novel immunotherapeutic strategies. This article aims to review the current status and emerging trends in macrophage immune regulation related to AS on a global scale.MethodsWe utilized the Web of Science Core Collection database to identify articles pertaining to macrophage immune regulation in AS published between 2000 and 2024. Bibliometric methods were used to analyze authors, institutions, countries, journals and references through CiteSpace and VOSviewer. A total of 1469 articles were included in this study.ResultsThe United States has published the highest number of articles in this field, followed closely by China. Maastricht University stands out as a leading institution specializing in macrophage immune regulation related to AS. Esther Lutgens from Germany has made significant contributions to this area of research. The authors identified “Arteriosclerosis, Thrombosis, and Vascular Biology” as the most influential journal within this domain. Through cluster analysis, the keywords were categorized into four primary groups: (1) autoantibodies, (2) activation, (3) immune activation, and (4) nuclear receptors.ConclusionThis study systematically summarizes the findings of macrophage immune regulation research in AS from 2000 to 2024, while also describing and predicting global research hotspots and trends. The investigation into the molecular mechanisms underlying macrophage immune regulation in AS is poised to become a prominent topic in future studies.